MicroRNA‐149 Negatively Regulates TLR‐Triggered Inflammatory Response in Macrophages by Targeting MyD88. Issue 5 (May 2014) - Xu, Guangxian; Zhang, Zhaobo; Xing, Yiwen; Wei, Jun; Ge, Zhaohui; Liu, Xiaoming; Zhang, Ying; Huang, Xuelan
ABSTRACT MicroRNAs (miRNAs) have been shown to be important regulators of TLR signaling pathway at the post‐transcriptional level. In this study, the potential role of miR‐149 was explored in murine alveolar macrophage RAW264.7 cells. Our results demonstrated a dynamic change of the expressions of miR‐149 expression and MyD88 in macrophage RAW264.7 upon Mycobacterium bovis Bacillus Calmette‐Guerlin (BCG) infection or lipopolysaccharide (LPS) stimulation. The presence of BCG or LPS dynamically reduced the miR‐149 expression, along with a substantially striking increase of MyD88 expression in these cells. More importantly, overexpression of miR‐149 in RAW264.7 cells was associated with a significant decrease of MyD88 protein expression, as well as a reduced production of inflammatory mediator NF‐κB 1, TNF‐α and IL‐6 in response to BCG infection or LPS stimulation. Further studies using immunoblotting assay against anti‐MyD88 antibody and microRNA targeting luciferase reporter assay revealed that miR‐149 was able to directly target the 3′‐UTR of MyD88 mRNA and post‐transcriptionally regulated MyD88 protein expression. These data suggested that miR‐149 might be a key player of immune modulator for TLR/MyD88 signaling pathway in macrophages, which may through a mechanism of negatively regulating MyD88‐dependent Toll‐like receptors signaling pathway. J. Cell. Biochem. 115: 919–927, 2014. © 2013 Wiley Periodicals, Inc.